Investigating the global productivity effects of highly skilled labour migration: how immigrant athletes impact Olympic medal counts - Horowitz, J.; McDaniel, S. R. (International Journal of Sport Policy and Politics, 2014)
Labour migration is a significant factor in today`s global economy, as more people live and work outside their country of birth than ever before. Elite athletes are among a select group of workers who can seek employment on a global market level and who offer data to assess how migration affects productivity. Similar to the concept of `brain drains and brain gains`, the migration of athletes also has policy implications. For example, there have been documented accounts of countries openly `recruiting` foreign athletes to help increase their Olympic medal counts. Although IOC officials have voiced concerns about such practices, they do not collect information tracking migration of Olympians (e.g. birthplaces, timing and relocation motives) or its potential effects on medal counts. This study represents the first known work to investigate labour migration patterns and productivity in the context of the Summer Olympics and has found preliminary evidence of migration`s effect in the four Summer Games of the twenty-first century. Among the key findings, percentage of medal winners who are immigrants is significantly higher than the current percentage of the world`s international migrant population. Results of hierarchical linear regression models predicting medal totals suggest that having immigrant athletes is one of the strongest indicators of medal totals for countries in each of the four Games. These findings highlight the challenges migration presents to current IOC policy.